US nuclear deterrence policy and its problems - Rudolf, Peter (2018)
Zusammenfassung: Nuclear deterrence is back. Of course, it had never disappeared, but retreated into the background as a hedge against future uncertainties. Hopes of overcoming the deterrence system through nuclear disarmament have been dashed. Nuclear deterrence gains new importance in the era of great power competitions. Arms control is stagnating, even eroding, and the modernisation of nuclear arsenals is progressing. Through nuclear sharing arrangements within the North Atlantic Treaty Organization (NATO), Germany is involved in nuclear deterrence. This includes the ability to deliver American nuclear bombs stored in Germany. So far, this has been ensured by nuclear-capable Tornado fighter bombers, due to be replaced in the foreseeable future. Against this background, nuclear deterrence and its strategic, legal, ethical, and political problems and dilemmas are assessed in this research paper. The focus is on US deterrence policy and its role in the Western alliance. This analysis of nuclear deterrence and its problems and dilemmas is intended to provide a basic orientation for the new nuclear debate that is emerging